2020
DOI: 10.3390/molecules25051170
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Composition and Biological Activity of Berries and Leaves from Four Romanian Sea Buckthorn (Hippophae Rhamnoides L.) Varieties

Abstract: Hippophae rhamnoides L. is an important source of natural antioxidant and antimicrobial agents. Phytochemical compounds, antioxidant and antibacterial properties of berries, and leaf extracts from four Romanian sea buckthorn cultivars were investigated. Large differences in the content of total polyphenols and flavonoids between the varieties were observed. HPLC analysis of the polyphenolic compounds showed greater differences in content in leaves than in berries. This study confirmed that sea buckthorn leaves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
64
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(72 citation statements)
references
References 57 publications
3
64
0
5
Order By: Relevance
“…The right line of defense is using substances that show strong antioxidant activity. Their activity is most often determined by the presence of polyphenolic compounds 1 4 , which have a positive effect on a number of enzyme systems and functional proteins, cell signaling or maintaining or restoring the redox balance, which can be disturbed as a result of oxidative stress 5 , 6 . Due to the multidirectional impact of antioxidants on the human body, the pharmaceutical and cosmetics industry has been looking for substances exhibiting strong antioxidant activity for many years.…”
Section: Introductionmentioning
confidence: 99%
“…The right line of defense is using substances that show strong antioxidant activity. Their activity is most often determined by the presence of polyphenolic compounds 1 4 , which have a positive effect on a number of enzyme systems and functional proteins, cell signaling or maintaining or restoring the redox balance, which can be disturbed as a result of oxidative stress 5 , 6 . Due to the multidirectional impact of antioxidants on the human body, the pharmaceutical and cosmetics industry has been looking for substances exhibiting strong antioxidant activity for many years.…”
Section: Introductionmentioning
confidence: 99%
“…It was observed that the quantities of flavonoids in these varieties could be ranked as follows: SF6 > Golden Abundant > Colosal > Carmen, and the ranked order for berry extracts was SF6 > Golden Abundant > Carmen > Colosal. Moreover, in all leaf extracts, the concentration and the differences in the content of FSBT were significantly greater than in the berry extracts (Criste et al, 2020). The content and variety information reflect the genetic diversities and environmental factors in synthesis and accumulation of FSBT in different species and can be helpful for the selection of highactivity cultivars related to FSBT and conditions for further cultivation.…”
Section: Phy Tochemis Trymentioning
confidence: 87%
“…Phenolic compounds also include primarily proanthocyanidins, gallocatechins and flavonol glycosides (Dienaitė, Pukalskas, Pukalskienė, Pereira, Matias, & Venskutonis, 2020) (Table 1). Criste et al, (2020) also reported that seabuckthorn berries are great source of phenolic compounds such as derivatives of quercetin and hydrocinnamic acid. (Criste et al, 2020).…”
Section: Compositionmentioning
confidence: 96%
“…Criste et al, (2020) also reported that seabuckthorn berries are great source of phenolic compounds such as derivatives of quercetin and hydrocinnamic acid. (Criste et al, 2020).…”
Section: Compositionmentioning
confidence: 96%
See 1 more Smart Citation